Characterisation of three-dimensional porosity in an Fe-based amorphous coating and its correlation with corrosion behaviour. (April 2015) - Zhang, S.D.; Zhang, W.L.; Wang, S.G.; Gu, X.J.; Wang, J.Q.
Graphical abstract: Highlights: The porosity in Fe-based amorphous coating is analysed quantitatively. The correlation between porosity and corrosion behaviour is investigated. Direct evidence of substrate corrosion caused by through-porosity is presented. Critical coating thickness for the presence of through-porosity is determined. Abstract: Porosity, an important and inevitable property of thermally sprayed coatings, considerably influences the corrosion resistance of the coated materials. In this work, the correlation between porosity and corrosion of an Fe-based amorphous coating was investigated. The volume fraction, size and distribution of the coating porosity were measured and analysed via 3D XRT technique. Direct evidence for preferential substrate corrosion caused by the through-porosity was obtained. It was found that through-porosity is sensitive to the coating thickness. The critical coating thickness for the presence of through-porosity was determined, which could provide a guide for the design of corrosion resistant coatings.